An exploratory study of the satisfaction towards the learning environment among adult distance learners in Mara University of Technology, Alor Gajah Campus / Rozman Md Yusof...[et.al] - Md Yusof, Rozman; Abd Aziz, Noor Azam; Ranjethamoney Vijayarajoo, Angeline; Salleh, Salmiah (Unit Penyelidikan dan Perundingan, 2003)
The aim of this study is to measure the level of satisfaction(if present), of the distance learners towards the learning environment in UiTM Alor Gajah Campus. Five aspects of learning satisfaction are looked at: rewards, social life, learning condition, recognition and quality of education. The researchers also looked at six independent variables : age, gender, marital status, working experience, income and program. A total of 186 questionnaires were distributed but only 178 were received. Data was analyzed using the Statistical Package for Social Science (SPSS). The results revealed that the majority of the respondents indicated an intermediate level of satisfaction towards the five aspects of the learning environment provided by the campus. Many adult learners met the satisfactory level of the CSSQ scale except for the learning condition aspect which was slight. It was also discovered that age, study level and marital status played a significant role in influencing learning satisfaction levels. Based on these results, it is recommended that the physical, psychological and sociological environment be improved. With all these, it is hoped that a conducive climate to adult learning will be established.